The effect of the exercises brain on boxers` eye-hand coordination, dynamic balance and visual attention performance - Cetin, O.; Beyleroglu, M.; Bagis, Y. E.; Suna, G. (Physical Education of Students, 2018)
Purpose: The purpose of this study is to investigate whether exercising brain performed by boxers have any kind of effect on visual attention, eye-hand coordination and dynamic balance performances of athletes. Material: In accordance with the purpose of this study, 29 athletes who do exercises regularly at Sakarya Boxing Club have been divided into two groups as control and experiment group. The Star Excursion Balance test was used to measure participants` dynamic balance performance, the Bourdon-Wiersma Stipple test was used to measure visual attention, and Alternate Hand Wall Toss test was used to measure eye-hand coordination as pre and posttest. Repeated Measures Anova analysis was used for analysis of the obtained data. Results: In terms of the obtained data, it has been observed that between pre and pro tests a significant development pattern shows itself for whole study group. On the other hand, as for the investigation of the pre and post-test interactions of experiment and control group, When pre and post-test interactions of experimental and control groups were examined, there was no significant difference in visual attention and dynamic balance development, but in eyehand coordination test, improvement in experimental group was found to be higher than in control group. Conclusions: The findings of the study in which exercising brain applied to boxers for 8 weeks showed that there was no significant difference between dynamic balance and visual attention development values, but there was a significant difference between control and experimental groups, eye-hand coordination development values.